A multidisciplinary STEM and liberal arts students-as-partners project promoted the development of employability skills and embodied partnership values - Lexis, Louise; Julien, Brianna; Loch, Birgit; Civitella, Mark; Keogh, Brianne; Boffa, Marc; Jelley, Tessa; Sawyer, Fiona; Ramadan, Selin; Pokhriyal, Pranita; Carpenter, Jarrod (International Journal for Students as Partners, 2023)
Few studies have explored student perceptions of participating in STEM multidisciplinary students-as-partners (SaP) projects integrated into the curriculum. We conducted content analysis on focus groups to determine partner perceptions of a STEM and liberal arts SaP project and used a mixed methods concurrent triangulation design to explore the degree to which partners thought the underpinning SaP values had been enacted. Four staff and seven students participated in the study. Perceptions of the project were aligned to four themes: outstanding student experience, development of student employability skills, a transformative change in the student-to-staff relationship, and barriers to success and enabling strategies. Qualitative and quantitative data indicated strong inclusion of the partnership values. This paper provides new insights into STEM and liberal arts SaP projects, indicating they may be well-suited to the embodiment of the underpinning SaP values, and help students prepare for the world of work.